RELATIONSHIPS BETWEEN SERUM URIC ACID AND BLOOD PRESSURE, METABOLIC VARIABLES AND CARDIOVASCULAR RISK PROFILE IN TREATED HYPERTENSIVE PATIENTS FROM CENTRAL AND EASTERN EUROPEAN COUNTRIES: RESULTS OF THE BP-CARE STUDY. (June 2018) - Redon, P.; Facchetti, R.; Maloberti, A.; Bombelli, M.; Redon, J.; Lurbe, E.; Mancia, G.; Grassi, G.
Abstract : Objective: Limited information is available on the association between serum uric acid (SUA) and metabolic syndrome, diabetes mellitus, renal failure, blood pressure (BP) control and cardiovascular (CV) risk profile in treated hypertensives of eastern European countries. Design and method: The BP-CARE study examined BP control and CV risk profile in about 8000 treated hypertensive patients followed by non-specialist or specialist physicians in Albania, Belarus, Bosnia, Czech Republic, Latvia, Romania, Serbia, Slovakia and Ukraine. In 3220 of them measurements included, along with clinic BP, 24-hour BP, metabolic and renal function variables, SUA values. Results: 51% were males, while mean age (±SD) was 60.0 ± 10.9 yrs, clinic BP 147.3 ± 18/87.8 ± 10 mmHg, 24 hour BP 137.3 ± 19/81.3 ± 10 mmHg and SUA values 5.68 ± 1.9 mg/dl, with a normal distribution in the population. SUA was significantly higher in males than females (5.99 ± 1.9 vs 5.34 ± 1.9 mg/dl, P < 0.0001) and progressively and significantly greater from the low to the medium, high and very high risk patients (4.87 ± 1.38 vs 5.85 ± 2.00, P < 0.0001, ESH CV risk categories). Significant differences were also found between diabetic and non-diabetic patients (5.92 ± 2.2 vs 5.58 ± 1.8, P < 0.0001), patients with and without metabolic syndrome (5.92 ± 2.1 vs 5.43 ± 1.7, P < 0.0001) and from stage 1 to stage 5 renal insufficiency (from 5.87 ± 2.0 to 10.48 ± 3.4, P < 0.0001). No significant difference in SUA was found between patients treated and non-treated with diuretic or angiotensin II blockers or in those under antihypertensive drug combination vs monotherapy. No difference in SUA was also found when analyzing the data in relation to clinic or 24-hour BP control. Conclusions: These data provide evidence that similarly to what described in western Europe, in central and eastern European countries SUA values are closely related to metabolic alterations, including diabetes mellitus, to renal insufficiency and CV risk profile. At variance from other studies, however, no relationship was found with BP control.